Hawkers Empowerment Strategy to Promote Sustainable Economy in Surakarta - Murtanti Jani Rahayu; Rufia Andisetyana Putri (International Conference on Engineering and Technology Development (ICETD), 2014)
Surakarta has implemented strategies of hawkers arrangement, such as relocation and stabilization. However, in 2012, after the arrangement, the number of hawkers increased not only new hawkers but also those who had been arranged before. They returned to illegal location due to perception that their needs were not accommodated. On the other side, hawkers’ needs are different depending on their commodity types. The correlation among the characteristics of hawkers by commodity types, hawkers’ involvement in arrangement process and the arrangement success, has prompted authors to develop hawkers empowerment strategies in Surakarta, which is adaptive to those components. The analysis was done by frequency distribution and descriptive techniques. The results of this study showed that the arrangement process has not been able to fully empower the hawkers. Strategies are then formulated into five groups according to the type of commodity: non-food, raw-food, consumed-at-place fast food, take-away fast food, and services.